NEURO TAXES: HOW TO INTERNALIZE TAX CULTURE FOR SUCCESSFUL MANAGEMENT OF TAXES? - Valencia Gutiérrez, Adolfo (2013)
The idea is to apply neuroscience to the internalization of the tax culture in the management of taxes by the Creditor and the Debtor with the corresponding Tax understanding Tribute birth, the birth of the obligation, enforceability and determination of taxes understand and apply equitable rights and obligations of the tax authorities and administered and the consistent application of sanctions in case of infringements liable for the incurred penalty or civil interdiction to incur if tax offenses established exhaustively in the tax rules. Surely synergistically to apply neuroscience and the theory of tax law, it is vital that neuroscience specialists think about the world of taxation and, in turn, that tax operators reflect on the world of neuroscience.